Dampak Implementasi Penggunaan Teknologi Manufaktur Tingkat Lanjut -Advanced Manufacturing Technology pada Kinerja UKM di Indonesia - Jani Rahardjo (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2014)
In Indonesia, 99.8% of the businesses are SMEs. However, those SMEs only contribute to the 56.7% of the Indonesia GDP.  This happened, mainly due to the limitations of SMEs which use traditional technologies in the production process. Therefore, in 2014, the Indonesian government through the Ministry of Cooperation and Small Medium Entreprises launced a new strategic plan to empowering the SMEs by applying the Advanced Manufacting Technology (AMT). It is believed that by applying the AMT in the SMEs can increase productivities, expand the market share and raised national economic growth. This study, identified the used of AMT in the Indonesia SMEs, especially in foods, beverages, herbal and handicraft sectors. Additionally, it is also measured the impact of the used of AMT in the SMEs’ performaces. In this study, it is found that 76.6 % of the total sampel (253 SMEs) declared that they use the AMT. This indicates that the Indonesia SMEs have a clear operation mission, process production, high quality products and meet the customer’s satisfaction. It is also found that the percentage of the hard technology is higher than the soft technology. This showed that there is a large effort to increase the productivity in the process production. Finally, we found that the impact of the AMT used to the SMEs’ performance in the market share, profitability and organization performance is increased significantly.